The Brain and Conscious Unity: Freud's Omega - Bob, Petr (Springer, 2016)
In this provocative text, a noted neuroscientist reexamines Freud's posthumously published Project of Scientific Psychology in the light of modern neuroscience. This expanded "thermodynamics of the mind" model includes robust conceptions of the cellular and neural processes that accompany creation of consciousness and memory, their contributions to such conditions as depression, dissociative disorders, and schizophrenia, and implications for practice, from imaging to talk-based therapies to pharmacotherapy. Central to this construct is Freud's proposal of specific "omega" neurons as the most volatile carriers of consciousness between mind and brain, which is applied to current issues regarding complexity and executive functioning. In addition, the book is extensively referenced, allowing readers to investigate these and related phenomena in greater detail.